Effect Of Lorazepam And Chlorpromazine On Food Intake In Budgerigars (Melopsittacus Undulatus) - Amir Safi , Hossein Hosseini , Hadi Haghbin Nazarpak (Migration Letters, 2024)
Anorexia is a nonspecific sign that has multiple etiologies. The absence of nutrition can lead to an increase risk of death. Appetite stimulant drugs can play a principle role in the control of anorexic birds. In budgerigars, lorazepam at a dosage of 1 mg/kg was shown to temporarily enhance hunger and provide a sedative effect that lasts for three hours. The low dose of lorazepam may be a better appetite stimulant, and less sedative than other doses of this drug, but currently, no information is available about it. Chlorpromazine is one of the antipsychotic drugs that can cause the weight gain in humans, and animals. So far, no information available for using the antipsychotic drugs as appetite stimulant in psittacine birds. Thirty adult Healthy budgerigars in a blinded, clinical trial, the effect intramuscular injection of chlorpromazine(0.1mg/kg)or lorazepam(0.5mg/kg,1mg /kg,2mg/kg) were compared to placebo treatment(1ml/kg).Abnormal behavior were recorded by a blinded observer to treatment. Lower dosage of lorazepam(0.5mg/kg) more increased food intake in budgerigar compare to lorazepam (1mg/kg,2mg/kg). Lorazepam(2mg/kg) has no effect increased appetite in budgerigar. Compared to the placebo and other treatment groups, the group taking chlorpromazine consumed a notably greater amount of food. The lorazepam groups showed evidence of drowsiness up to two hours after the treatment, whereas the chlorpromazine and placebo groups showed no signs of sedation.